ATRT-32. GENOME-WIDE CRISPR AND SMALL-MOLECULE SCREENS UNCOVER TARGETABLE DEPENDENCIES IN AT/RTs. (4th December 2020) - Merk, Daniel; Hirsch, Sophie; Walter, Bianca; Häusser, Lara; Persky, Nicole; Root, David; Schüller, Ulrich; Tabatabai, Ghazaleh
Abstract: Brain tumors are the leading cause of cancer-related deaths in children and adolescents. Embryonal brain tumors are a group of high-grade neoplasms which primarily affect young patients, and atypical teratoid rhabdoid tumors (AT/RTs) are the second most common type of tumor within this group. In spite of intensive research efforts and the knowledge of molecular mechanisms driving subgroup-specific heterogeneity within ATRTs, survival estimates stay relatively low as compared to other tumor entities with a median survival of around 17 months. More efficacious and durable therapies are urgently needed to improve the situation of patients. We here used a combination of genome-wide CRISPR dependency screens and small-molecule drug assays to identify genetic vulnerabilities and novel therapeutic targets for this tumor entity. Here, we successfully generated a chemical library that shows preferential activity in AT/RT cell lines, thereby validating our CRISPR approach to identify tumor-specific vulnerabilities. Of note, none of the identified dependencies seemed to be subgroup-specific, suggesting that targets identified here can be used as pan-AT/RT therapeutic avenues. Among others, these include inhibition of EGF signaling and CDK4/6. Our data provide a comprehensive map of dependencies for AT/RTs which will serve as a starting point in the development of targeted therapies for this tumor entity.